KAJIAN FAKTOR-FAKTOR YANG MENDUKUNG DAN TIDAK MENDUKUNG PERLUASAN LAYANAN BUS RAPID TRANSIT (BRT) TRANS JATENG (Studi Kasus: Koridor 1 Bawen ”“ Tawang Rute Menjadi Salatiga ”“ Tawang) - Nugraheni, Desi Wulan; Rochim, Abdul; Karlinasari, Rinda (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The high public interest in the Semarang City, Semarang Regency, and Salatiga City areas towards the Trans Jateng BRT service has become the basis for the expansion of the Trans Jateng BRT service from corridor 1 Bawen-Tawang route to Salatiga-Tawang, which is much needed. Therefore, the aim of this research is to identify factors that support and oppose the expansion of the Trans Jateng BRT service from corridor 1 Bawen-Tawang route to Salatiga-Tawang and to find appropriate strategies to address the differences between supporting and opposing factors for the expansion of this service. This study employs a descriptive qualitative approach using the Delphi method and SWOT analysis. The research findings indicate that there are 24 factors supporting the expansion of the Trans Jateng BRT service, categorized into transportation infrastructure availability, community support, regional development plans, economic factors, government support, and the success of the Trans Jateng service. There are 15 factors opposing the expansion of the Trans Jateng BRT service, categorized into transportation infrastructure inadequacy, stakeholder disagreement, budget constraints and financial resources limitations, as well as low public awareness and education. The strategy to address the differences between supporting and opposing factors for the expansion of the Trans Jateng BRT service from corridor 1 Bawen-Tawang route to Salatiga-Tawang is the stable growth strategy.